Art Features of Du’s poems - Esbolat, Т (Journal of Oriental Studies, 2016)
Du Fu is one of the outstanding representatives of poets during the golden era of the Tang dynasty. He is well-known of his poems with typical realistic art features. The artistic content of his poems are in deep thoughts and expression, and fully revealed the realities of his time. Metaphor method is used in a variety of ways, and changes in different forms, which become one of the eastern routine ways in Chinese literature later. His poems coveres the reality of civilian life, and reveals the truth during his lifetime using his specific art features in his poems.